2015
DOI: 10.1590/0100-2945-210/14
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Sugar-Acid Ratio and Relevant Metabolizing Enzyme Activities in Navel Orange Fruits From Different Eco-Regions

Abstract: -The flavor quality of citrus fruits is largely determined by the sugar-acid ratio, but it remains uncertain how sugar-and/or acid-metabolizing enzymes regulate the sugar-acid ratio of navel oranges and further affect the fruit quality. In the present study, Robertson navel oranges (Citrus sinesis osb.) were collected from six representative habitats in three eco-regions of Sichuan, China. The changes in the sugar-acid ratio and the activities of sucrose phosphate synthase (SPS), sucrose synthase (SS), cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Citrate synthase has a positive relation with citric acid accumulation in fruits [39,40]. Our results showed that the activity of CS in both cultivars decreased from fruitlet stage to green stage and then increased at later stages.…”
Section: Discussionmentioning
confidence: 53%
“…Citrate synthase has a positive relation with citric acid accumulation in fruits [39,40]. Our results showed that the activity of CS in both cultivars decreased from fruitlet stage to green stage and then increased at later stages.…”
Section: Discussionmentioning
confidence: 53%
“…It contributes towards giving many fruits their characteristic flavor. It is also an indicator of commercial and sensory ripeness (Kelebek and Selli, 2011;Ronggao et al, 2015). These SSC results of eight Aprikoz accessions are claimed that enough genetic diversity exists in Aprikoz accessions to mitigate the adverse effects of climate warming on fruit quality.…”
Section: Resultsmentioning
confidence: 98%